2018
DOI: 10.22159/ijap.2018v10i4.24823
|View full text |Cite
|
Sign up to set email alerts
|

Complex Technological and Biological Research of Solutions for Peritoneal Dialysis

Abstract: Objective: The purpose of our work was to conduct technological, analytical, and biological investigations and stability studies of peritoneal dialysis (PD) solutions containing glucose and sodium lactate in single-chamber containers.Methods: Different formulations of PD solutions were prepared and sterilized at a temperature of 121 °C during 15 m. UV-spectrophotometric determination was performed using purified water as a blank. The spectra of the solutions were run in the range of 220 to 400 nm for the ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Each mL of 0.1 M silver nitrate is equivalent to 3.545 mg of Cl -. The content of chloride ions (X 1 ), in mmol/L, in a solution, is calculated according to the following formula: X 1 = V 1 ∑ K ∑ 3.545 ∑ 1000 : 10 : 35.45 = V 1 ∑ K ∑ 10, where V 1 is a volume of 0.1 M solution of silver nitrate used in the titration of a tested solution, in ml, respectively; K is a correction coefficient to the molarity of 0.1 M solution of silver nitrate (7).…”
Section: Analytical Procedures Of Direct Argentometric Methods For the mentioning
confidence: 99%
See 2 more Smart Citations
“…Each mL of 0.1 M silver nitrate is equivalent to 3.545 mg of Cl -. The content of chloride ions (X 1 ), in mmol/L, in a solution, is calculated according to the following formula: X 1 = V 1 ∑ K ∑ 3.545 ∑ 1000 : 10 : 35.45 = V 1 ∑ K ∑ 10, where V 1 is a volume of 0.1 M solution of silver nitrate used in the titration of a tested solution, in ml, respectively; K is a correction coefficient to the molarity of 0.1 M solution of silver nitrate (7).…”
Section: Analytical Procedures Of Direct Argentometric Methods For the mentioning
confidence: 99%
“…Peritoneal dialysis (PD) is an essential life-sustained treatment modality of renal replacement the-rapy, which is documented to cost less to health care systems in the world compared with hemodialysis (7,8). To the best of our knowledge, scientific papers do not provide information on pharmaceutical development including analytical aspects of PD solutions of the first or second generations despite increasing the prevalence of PD patients in developed and developing countries.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of RRT is limited in many countries with a high burden of CKD (Hill et al 2016;Hudz et al 2018a;Lv and Zhang 2019). The development and manufacture of solutions for dialysis therapy (concentrates for HD and solutions for PD) in a country will permit to reduce their cost mainly because of the absence of international deliveries.…”
Section: Renal Replacement Therapymentioning
confidence: 99%
“…Data also showed that there were 2 million death cases of CKD because of the limited access in renal replacement therapy [6]. CKD is often associated with reduced quality of life due to its complications [7]. Hemodialysis in CKD is performed to replace kidney function in end-stage renal disease.…”
Section: Introductionmentioning
confidence: 99%